Engineering drawing and design - Madsen, David A. (Delmar, 1996)
This is acknowledged as the most comprehensive and accurate engineering drafting book on the market. This outstanding resource spans the engineering disciplines to include coverage of welding processes, fluid power, and industrial piping, as well as civil, electrical/electronic, and HVAC/sheet metal drafting. This text remains on the cutting edge with current ANSl/ASME standards throughout and updated CAD applications, ensuring your exposure to the most current technology. It serves as an excellent core text for engineering and drafting technology students as well as an ideal reference for professional engineers.